Some New Fractional Inequalities Defined Using cr-Log-h-Convex Functions and Applications - Mehmood, Sikander; Mohammed, Pshtiwan Othman; Kashuri, Artion; Chorfi, Nejmeddine; Mahmood, Sarkhel Akbar; Yousif, Majeed A. (Symmetry (Basel), 2024)
There is a strong correlation between the concept of convexity and symmetry. One of these is the class of interval-valued cr-log-h-convex functions, which is closely related to the theory of symmetry. In this paper, we obtain Hermite–Hadamard and its weighted version inequalities that are related to interval-valued cr-log-h-convex functions, and some known results are recaptured. To support our main results, we offer three examples and two applications related to modified Bessel functions and special means as well.